2023
DOI: 10.47280/revfacagron(luz).v40.n3.02
|View full text |Cite
|
Sign up to set email alerts
|

Water productivity using furrow and drip irrigation in hybrid maize

Abstract: Agriculture is the economic sector that consumes around 70 % of the total water extracted globally, considering itself a victim of its own inefficiency. The present work was oriented to look for irrigation alternatives that allow a greater productivity of water. The trial was carried out at the Faculty of Agricultural Sciences, Technical University of Machala, Ecuador. The amount of water applied to the corn crop through furrow and drip irrigation was evaluated. The treatments were: furrow irrigation, superfic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This was studied by J. Conde et al (2023). During their study, it was revealed that subsurface drip irrigation to a depth of 20 cm had a water productivity of 8.23 kg/m³, which was the best compared to furrow irrigation and surface drip irrigation and achieved a high olive yield of 9.3 t/ha.…”
Section: Discussionmentioning
confidence: 99%
“…This was studied by J. Conde et al (2023). During their study, it was revealed that subsurface drip irrigation to a depth of 20 cm had a water productivity of 8.23 kg/m³, which was the best compared to furrow irrigation and surface drip irrigation and achieved a high olive yield of 9.3 t/ha.…”
Section: Discussionmentioning
confidence: 99%
“…This was studied by J. Conde et al (2023). During their study, it was revealed that subsurface drip irrigation to a depth of 20 cm had a water productivity of 8.23 kg/m³, which was the best compared to furrow irrigation and surface drip irrigation and achieved a high olive yield of 9.3 t/ha.…”
Section: Discussionmentioning
confidence: 99%
“…The groundwater extracted from the three wells can be used for irrigation; however, there is a need to evaluate the situation presented in some parameters to improve water quality. In this sense, Conde et al (2023) pointed out that irrigation alternatives should be sought that allow greater water productivity, evaluating the amount of water applied to crops through irrigation, with a control of the irrigation regime, the volume of water applied and the yield.…”
Section: Physical Chemical and Microbiological Analysesmentioning
confidence: 99%